The land of stories the wishing spell - Colfer, Chris (The land of stories, 2017)
Alex and Connor Bailey's world is about to change. When the twins' grandmother gives them a treasured fairy-tale book, they have no idea they're about to enter a land beyond all imagining: The Land of Stories, where fairy tales are real. The twins know they must get back home somehow. But with the legendary Evil Queen hot on their trail, will they ever find the way?